High temperature mechanical properties of WC–Co hard metals. (April 2016) - Teppernegg, T.; Klünsner, T.; Kremsner, C.; Tritremmel, C.; Czettl, C.; Puchegger, S.; Marsoner, S.; Pippan, R.; Ebner, R.
Abstract: Understanding of the load situation and consequently the lifetime of cutting tools made of WC–Co hard metal requires quantitative data for thermo-mechanical properties. For the elevated temperatures present in application, these data are currently rather rare. The present work does discuss elastic material properties up to 1100 °C and compressive yield strength up to 900 °C, both as a function of Co content. The fracture toughness was determined as a function of the WC grain size and Co content up to 800 °C. Young's modulus and yield strength decrease with increasing temperature. A significant rise in fracture toughness was observed at 800 °C with increasing Co content and decreasing WC grain size. A possible reason for this increase is an increase in the plastic zone size at elevated temperatures. Highlights: Elastic properties, yield strength and fracture toughness are determined dependent on temperature. Young's and shear modulus decrease with increasing temperature and Co content. No influences of WC grain size on Young's and shear modulus and Poisson's ratio. Yield strength decreases with increasing temperature and increasing Co content. At 800 °C WC–Co grades with higher Co content show significant increase in fracture toughness.